2019
DOI: 10.1111/maec.12565
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐ and size‐associated differences in the skeletal structures and osculum cross‐sectional area influence the pumping rate of contractile sponge Cinachyrella cf. cavernosa

Abstract: Sponges alter the proportion of structural and morphological components such as spicule skeleton and number of oscula in response to environment, development and growth. Such mechanisms indicate morphological and physiological variations within populations. We measured the pumping rate of different sized specimens of contractile sponge Cinachyrella cf. cavernosa present in the intertidal rock pools, during morning and afternoon low tides along the central west coast of India. Additionally, we measured the exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
(138 reference statements)
3
7
0
Order By: Relevance
“…This hypothesis is supported by observations in Cinachyrella cf. cavernosa where the number of choanocyte chambers increased only marginally with the increase in sponge volume (Dahihande and Thakur, 2019).…”
Section: Mechanisms Underlying the Relationship Between Pumping Rate mentioning
confidence: 91%
See 4 more Smart Citations
“…This hypothesis is supported by observations in Cinachyrella cf. cavernosa where the number of choanocyte chambers increased only marginally with the increase in sponge volume (Dahihande and Thakur, 2019).…”
Section: Mechanisms Underlying the Relationship Between Pumping Rate mentioning
confidence: 91%
“…This decrease may be associated with an increase of the density of structural elements (e.g., spicules) that is required to stabilize and strengthen the larger and often higher structure and also to the need for larger canals. Structural differences were observed between different species (Turon et al, 1997) and empirical data showed that differences in the amount of spicules may vary with sponge volume (Barthel and Theede, 1986;Bavestrello et al, 2000;Dahihande and Thakur, 2019). Further studies are needed to explore the variation of structural and functional units over sponge size and age in relation to sponge pumping.…”
Section: Mechanisms Underlying the Relationship Between Pumping Rate mentioning
confidence: 99%
See 3 more Smart Citations